A general solution for scattering by infinite cylinders in the presence of an interface. (September 2019) - Lee, Siu-Chun
Highlights: Presented solution for scattering by multiple cylinders located in front of, behind, and on both sides of an interface. Accounted for depolarization, near-field scattering, surface interaction, and coupling across interface in formulation. Demonstrated the deduction of solutions for all scattering scenarios by cylinders from the present formulas. Illustrated scattering by coated and perfectly conducting cylinders in the near- and far-fields by numerical examples. Abstract: A general solution for scattering by multiple parallel infinite cylinders in the presence of a half space interface is presented in this paper. The cylinders are located in either or both half spaces, which are irradiated by a homogeneous or evanescent source wave traversing in a direction inclined from the axes of the cylinders. The theoretical approach is an exact analytical treatment that accounts for depolarization at oblique incidence, near-field scattering between cylinders, interaction with reflected waves from the interface, and coupling of cylinders across the interface. The electromagnetic fields are formulated using Hertz potenials that are expanded in terms of cylindrical wave functions. The unknown expansion coefficients are determined by boundary matching. Analytical formulas are derived for the electromagnetic fields and Poynting vector of scattered radiation in the far field. Application of the present solution to all scenarios of scattering by cylinders in the presence of a half space interface is illustrated analytically and by numerical examples.